Facile and greener hydrothermal honey-based synthesis of Fe3 O 4 /Au core/shell nanoparticles for drug delivery applications - Rasouli, Elisa; Basirun, Wan Jefrey; Johan, Mohd Rafie; Rezayi, Majid; Darroudi, Majid; Shameli, Kamyar; Shanavaz, Zohreh; Akbarzadeh, Omid; Izadiyan, Zahra (John Wiley & Sons, 2018)
In the present research, we report a greener, faster, and low-cost synthesis of gold-coated iron oxide nanoparticles (Fe 3 O 4 /Au-NPs) by different ratios (1:1, 2:1, and 3:1 molar ratio) of iron oxide and gold with natural honey (0.5% w/v) under hydrothermal conditions for 20 minutes. Honey was used as the reducing and stabilizing agent, respectively. The nanoparticles were characterized by X-ray diffraction (XRD), UV-visible spectroscopy, field emission scanning electron microscope (FESEM), energy-dispersive X-ray spectroscopy (EDXS), transmission electron microscopy (TEM), selected area electron diffraction (SAED), vibrating sample magnetometer (VSM), and fourier transformed infrared spectroscopy (FT-IR). The XRD analysis indicated the presence of Fe 3 O 4 /Au-NPs, while the TEM images showed the formation of Fe 3 O 4 /Au-NPs with diameter range between 3.49 nm and 4.11 nm. The VSM study demonstrated that the magnetic properties were decreased in the Fe 3 O 4 /Au-NPs compared with the Fe 3 O 4 -NPs. The cytotoxicity threshold of Fe 3 O 4 /Au-NPs in the WEHI164 cells was determined by using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. It was demonstrated no significant toxicity in higher concentration up to 140.0 ppm which can become the main candidates for biological and biomedical applications, such as drug delivery. © 2018 Wiley Periodicals, Inc.